Supramolecular organization of fucoxanthin-chlorophyll proteins in centric and pennate diatoms - Gardian, Zdenko; Litvín, Radek; Bína, David; Vácha, František (Photosynthesis research, 2014)
Fucoxanthin-chlorophyll proteins (FCP) are the major light-harvesting proteins of diatom algae, a major contributor to marine carbon fixation. FCP complexes from representatives of centric (Cyclotella meneghiniana) and pennate (Phaeodactylum tricornutum) diatoms were prepared by sucrose gradient centrifugation and studied by means of electron microscopy followed by single particle analysis. The oligomeric FCP from a centric diatom were observed to take the form of unusual chain-like or circular shapes, a very unique supramolecular assembly for such antennas. The existence of the often disputed oligomeric form of FCP in pennate diatoms has been confirmed. Contrary to the centric diatom FCP, pennate diatom FCP oligomers are very similar to oligomeric antennas from related heterokont (Stramenopila) algae. Evolutionary aspects of the presence of novel light-harvesting protein arrangement in centric diatoms are discussed.
Keywords: rozsivky; Thylakoids; proteiny vázající chlorofyl; transmisní elektronová mikroskopie; tylakoidy; Diatoms; Microscopy, Electron, Transmission; Chlorophyll Binding Proteins